Effects of Forest Fragment Area on Interactions Between Plants and Their Natural Enemies: Consequences for Plant Diversity at Multiple Spatial Scales - Viswanathan, Ashwin; Ghazoul, Jaboury; Lewis, Owen T.; Honwad, Ganesh; Bagchi, Robert (Frontiers in Forests and Global Change, 2020)
Density-dependent interactions between plants and their natural enemies, including fungal pathogens and insect herbivores, help maintain plant species coexistence and diversity at local scales (α-diversity). However, turnover in plant species composition across space also contributes to biodiversity at larger spatial scales (β-diversity). Despite mounting evidence that enemies can maintain α-diversity, we know little about their contributions to β-diversity. Additionally, in the light of widespread habitat fragmentation and potentially modified insect and pathogen communities in forest fragments, the effects of fragment area on their diversity-maintaining roles are largely unknown. We carried out a field experiment to investigate how natural enemies in impact tree α and β-diversity in a fragmented rainforest landscape in the Western Ghats, India. In twenty-one rainforest fragments, we suppressed insects and fungi/oomycetes with pesticides, and examined changes in the diversity of tree seedlings. We found that fungicide had no effect on α-diversity, but significantly decreased β-diversity (species turnover among plots). The facilitative effects of fungi and oomycetes on β-diversity, however, weakened as fragments decreased in area, indicating that certain specialized plant-pathogen interactions may be lost when fragments become smaller. Insecticide, in contrast, increased α-diversity. However, insects tended to increase β-diversity between distant plots. In summary, we found that interactions between plants and their natural enemies help maintain β-diversity in large forest fragments but not in small fragments. Small fragments are often viewed as future reservoirs of biodiversity in human-dominated landscapes, but our findings suggest that modified interactions with natural enemies may result in the erosion of this diversity over time.